2019
DOI: 10.4317/medoral.22955
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of systematic reviews regarding dental implant placement on diabetic patients: an overview of systematic reviews

Abstract: Background Since implant placement on diabetic patients still is a controversial topic and systematic reviews are at the top of scientific evidence hierarchy, a thorough assessment of the methodological quality of these reviews must be performed to inform clinicians if their conclusions and recommendations can be followed on clinical practice. An overview of systematic reviews was performed with the purpose to assess the methodological quality of systematic reviews regarding dental implant placeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In five studies, no clear conclusion could be drawn from the data obtained, so that the question of an increased risk was not answered [ 10 , 25 , 33 , 43 , 64 ]. However, the available aggregated literature consistently concluded that diabetes mellitus represents a risk factor for the development of peri-implant inflammation, although most studies point to a lack of high-quality and long-term studies on this research area [ 8 , 50 , 51 , 54 56 , 58 , 60 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…In five studies, no clear conclusion could be drawn from the data obtained, so that the question of an increased risk was not answered [ 10 , 25 , 33 , 43 , 64 ]. However, the available aggregated literature consistently concluded that diabetes mellitus represents a risk factor for the development of peri-implant inflammation, although most studies point to a lack of high-quality and long-term studies on this research area [ 8 , 50 , 51 , 54 56 , 58 , 60 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…As for implant survival rates, the present study did not find any association with diabetes. A recent review published by Oliveira-Neto et al in 2019 [5] came to the same conclusion, reporting that diabetes did not affect implant survival rate in two meta-analyses of high methodological quality [18,19]. Chrcanovic et al [18] analyzed a total of 604 subjects (49 diabetic, 555 non-diabetic) and reported an RR of 1.07, while Moraschini and Barboza [19] analyzed a total of 2334 subjects (802 diabetic, 1532 non-diabetic), with an RR of 1.43 and 3.65 for type 1 and type 2 DM, respectively; it must be noted that in all the included studies diabetes was under control at the time of the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…While diabetes has been proven as an important risk factor for periodontitis, its association with peri-implant diseases has not been fully explored, and the existing literature reports controversial results. Some hypotheses of how diabetes could interfere with implant success have been formulated, and these include: the suppression of osteoblastic differentiation, proliferation and activity, deficits in the healing process, and the alteration of the immune response [5].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple recent publications have addressed the topic of methodological quality of systematic reviews in dentistry [ 10 ] including the fields of neuromuscular dentistry [ 11 ], implant dentistry [ 12 14 ], periodontology [ 15 , 16 ], orthodontics [ 17 ], endodontics [ 18 ] and oral and maxillofacial surgery [ 19 ]. In these studies, there was substantial lack of adherence to considered critical methodological quality domains [ 8 ].…”
Section: Introductionmentioning
confidence: 99%